Validation of Using a Modified BET Model to Predict the Moisture Adsorption Behavior of Bituminous Coal. Issue 1 (2nd January 2016) - Strydom, C. A.; Campbell, Q. P.; le Roux, M.; du Preez, S. M.
Abstract : A good correlation exists between the amount of moisture adsorbed and the oxygen content of medium-rank B vitrinite-rich and medium-rank C inertinite-rich bituminous coal. Total mass moisture adsorbed per gram of coal determined from the modified BET model provides a better approximation than the BET model. The relationship between the modified BET moisture monolayer coverage and the area of surface oxygen groups suggests that moisture is adsorbed at these sites. Oxygen content is a good indicator of the amount of moisture adsorbed on bituminous coal. Open hysteresis loops indicate that moisture is retained on medium-rank C inertinite-rich bituminous coals.